Complex Bench Surgery Does Not Increase the Risk of Vascular Complications after Pediatric Kidney Transplantation - Ghidini, Filippo; Fascetti Leon, Francesco; De Corti, Federica; Meneghesso, Davide; Longo, Germana; Sgrò, Alberto; Michelon, Stefania; Metrangolo, Salvatore; Meneghini, Luisa; Castagnetti, Marco; Benetti, Elisa; Gamba, Piergiorgio; Dall'Igna, Patrizia (European Journal of Pediatric Surgery, 2022)
Introduction Vascular complications are severe complications of pediatric kidney transplantation (KT). We aimed to investigate whether a complex bench surgery (BS) affects the outcomes.Methods All pediatric KT performed at the University Hospital of Padua from 2015 to 2019 were analyzed, comparing those in which a standard BS was possible to those that necessitated a complex BS. The rates of vascular complications, patients' outcome, and graft survival were compared in the two groups.Results Eighty KTs were performed in 78 patients with a median age of 11 years (interquartile range [IQR] 4.3–14) and a median body weight of 24 kg (IQR 13–37). Thirty-nine donor kidneys (49%) needed a complex BS due to anomalies of renal veins in 12 (31%) and renal arteries in 16 (41%). The remaining 11 grafts (28%) underwent an elongation of the vein. There was no difference in the rate of primary graft non function (p = 0.97), delayed graft function (p = 0.72), and overall survival (p = 0.27). The rates of vascular complications, bleedings, and venous graft thrombosis were similar (p = 0.51, p = 0.59, p = 0.78, respectively). No arterial thrombosis or stenosis was reported.Conclusion Complex BS did not compromise survival of the graft and did not put the allograft at risk of vascular complications, such as bleedings or thrombosis.
Keywords: kidney transplantation; bench surgery; graft thrombosis; graft survival; vascular complications